The unique association between the level of peripheral blood monocytes and the prevalence of diabetic retinopathy: a cross-sectional study - Heng Wan; Yan Cai; Yuying Wang; Sijie Fang; Chi Chen; Yi Chen; Fangzhen Xia; Ningjian Wang; Minghao Guo; Yingli Lu (Journal of Translational Medicine, 2020)
Abstract Objective The attraction and influx of monocytes into the retina has been considered a critical step in the development of diabetic retinopathy (DR). However, large population studies about the association between peripheral blood monocyte levels, an inexpensive and easily measurable laboratory index, and DR are limited. Thus, we aimed to investigate the association between peripheral blood monocyte levels and DR. Methods A total of 3223 participants out of 3277 adults with diabetes were enrolled from seven communities in China in this cross-sectional survey. Participants underwent several medical examinations, including the measurement of anthropometric factors, blood pressure, routinely analyzed leukocyte characteristics, glucose, lipid profiles, urine albumin/creatinine ratio and fundus photographs. Results The prevalence of DR among the participants in the highest quartile of peripheral blood monocyte levels significantly decreased by 41% (OR 0.59; 95% CI 0.43, 0.81) compared with the participants in the first quartile (P for trend < 0.05). However, there were no associations between the monocyte level and the prevalence of cardiovascular and cerebrovascular diseases (CVD) and diabetic kidney disease (DKD) (both P for trend > 0.05). Associations between leukocyte, neutrophil and lymphocyte levels and DR were also not found (all P for trend > 0.05). These associations were all fully adjusted for age, sex, education status, duration of diabetes history, current smoking, BMI, HbA1c, dyslipidemia, systolic blood pressure and insulin therapy. Conclusion Decreased peripheral blood monocyte levels were associated with increased odds of DR after adjusting for potential confounders in diabetic adults. However, causation remains to be demonstrated.